Parameterising the E-ELT point spread function for science simulations with HARMONI - Zieleniewski, S; Thatte, N (INAF - Osservatorio Astrofisico di Arcetri Largo Enrico Fermi, 2013)
With the first ELTs around the corner it is becoming ever more important to determine observational strategies and assess the prospective success of observing programs prior to making the observations. To this end, scientific simulations need to become more refined to understand the criteria required for a specific science case. We address the science simulations for HARMONI, an AO assisted first light integral field spectrograph (IFS) for the E-ELT. AO point spread functions (PSFs) vary markedly as a function of wavelength and type of AO system used, so there is need to create detailed PSFs across all IFS wavelength channels for accurate simulations. Detailed AO simulations have shown that for LTAO on the E-ELT, Strehl ratios can vary from 0.5% in V-band up to 75% in K-band. Using a single PSF for an entire datacube (especially with large instantaneous wavelength coverage) could introduce misleading features into simulated observations using HARMONI. We have developed a method to parameterise detailed PSFs using analytical models, which can then be interpolated as a function of wavelength. This allows us to create accurate, but computationally inexpensive, AO PSF datacubes for HARMONI simulations. This shall be developed to cover LTAO, SCAO and GLAO/no-AO PSFs.